Standardization of the Pharmaceutical Substance of the Drug LCS-1208 - E. V. Ignateva (Разработка и регистрация лекарственных средств, 2021)
Introduction. Indolocarbazole derivatives are of increasing scientific interest for practical oncology. A number of N-glycosides, indolo[2,3-a] carbazole under the laboratory code LCS, were synthesized in the laboratory of chemical synthesis of the National Medical Center of Oncology named after N.N. Blokhin. Currently, one of the most promising compounds in this class is LCS-1208, a representative of the arabinoside class of indolo [2,3-a]pyrrolo[3,4-c]carbazole-5,7-dione. According to the mechanism of biological action, LCS-1208 is a protein kinase C inhibitor and is of great interest for the treatment of malignant neoplasms.Aim. Chemical and pharmaceutical standardization of the pharmaceutical substance LCS-1208.Materials and methods. Laboratory samples of pharmaceutical substance LCS-1208. Methods of investigation: gravimetry, spectrophotometry, polarimetry, high-performance liquid chromatography (HPLC), high-resolution nuclear magnetic resonance (NMR) spectroscopy and infrared (IR) spectroscopy.Results and discussion. The quality assessment of LCS-1208 was carried out according to the indicators adopted in the XIV edition of the State Pharmacopoeia of the Russian Federation for quality control of pharmaceutical substances. LCS-1208 - orange amorphous powder, odorless; soluble in dimethylsulfoxide (DMSO) and dimethylformamide (DMF); very slightly soluble in 95 % ethyl alcohol and practically insoluble in water. The authenticity of the substance is confirmed by NMR and IR spectra, as well as electronic absorption spectra. The values of the specific optical rotation of LCS-1208 (1 % solution in DMF) are placed in the range from +58° to +61°. All the studied samples of the substance were free of inorganic impurities, sulphate ash, heavy metals and contained no more than 1.0 % water, determined by the K. Fischer titration method. The content of possible related impurities in the substance LCS-1208 and the content of the main active substance were determined by HPLC. The studied laboratory series of the pharmaceutical substance LCS-1208 contained no more than 1.0 % of any single and no more than 3 % of the total unidentified impurities. The content of the main active substance was more than 97 %.Conclusion. As a result of the work carried out, quality criteria and parameters were selected and methods for their determination were developed, which allow to adequately assess the quality and standardness of the pharmaceutical substance LCS-1208.